Accuracy of glucose meters in measuring low blood glucose levels - Lulin Choubtum (2018)
Background: Hypoglycemia is an emergency condition requiring treatment as soon as possible. Therefore, rapid and reliable blood glucose measurements are necessary. There are 2 systems of glucose meters (GMs), the reflectance photometer system (RPS) and the electrochemical biosensor system (BSS). GMs are widely used in monitoring blood glucose (BG) in patients with diabetes. BG values measured by GMs have been confirmed to be accurate especially in measuring normal and high BG levels. However, the data on the accuracy of GMs in measuring low BG levels are limited. Objective: To compare accuracy and reliability of different systems of GMs in the measurement of low BG values. Patients and Method: Venous and capillary whole blood specimens were collected from patients who were investigated for pituitary dysfunction. The patients underwent an insulin-induced hypoglycemia test by intravenously administering human regular insulin. The low BG level was defined as having venous plasma glucose (PG) of less than 60 mg/dl (mean ± SD = 36.59 ± 9.19, n = 54). Capillary blood samples were obtained from fingertips. Venous BG (vBG) and capillary BG (cBG) were measured by GMs. Venous PG which considered a reference value was measured by the glucose dehydrogenase method. Results: The correlation coefficient (r) between vBG measured by GMs-RPS and PG was 0.86 (p<0.001), whereas, that between vBG by GMs-BSS and PG was 0.75 (p<0.001). Similarly, the r between cBG by GMs-RPS and PG was 0.73 (p<0.001), whereas, that between cBG by GMs-BSS and PG was 0.69 (p<0.001). The mean difference between vBG by GMs-RPS and PG values was 0.01 ± 4.90 mg/dl, whereas, that between vBG by GMs-BSS and PG values was 10.50 ± 7.07 mg/dl which was significantly greater than the former (p<0.001). Moreover, the mean difference between cBG by GMs-RPS and PG values was 14.45 ± 8.76 mg/dl, whereas, that between cBG by GMs-BSS and PG values was 23.87 ± 9.48 mg/dl which was also significantly greater than the former (p<0.001). These results demonstrated that vBG measured by GMs-RPS was comparable to PG values. In addition, cBG values by GMs-RPS and GMs-BSS were approximately 14 mg/dl or 38 per cent and 24 mg/dl or 65 per cent greater than PG values, respectively. Conclusion: In measuring low blood glucose levels, glucose meters using the reflectance photometer system are more accurate than those using the electrochemical biosensor system.